A fully on-chip fast-transient NMOS low dropout voltage regulator with quasi floating gate pass element. (April 2017) - Wang, Han; Gou, Chao; Luo, Kai
Abstract: This paper presents a fully on-chip NMOS low-dropout regulator (LDO) for portable applications with quasi floating gate pass element and fast transient response. The quasi floating gate structure makes the gate of the NMOS transistor only periodically charged or refreshed by the charge pump, which allows the charge pump to be a small economical circuit with small silicon area. In addition, a variable reference circuit is introduced enlarging the dynamic range of error amplifier during load transient. The proposed LDO has been implemented in a 0.35 μ m BCD process. From experimental results, the regulator can operate with a minimum dropout voltage of 250 mV at a maximum 1 A load and I Q of 395 μ A. Under full-range load current step, the voltage undershoot and overshoot of the proposed LDO are reduced to 50 and 26 mV, respectively.